2019
DOI: 10.1108/srj-03-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Business strategy for environmental social governance practices: evidence from telecommunication companies in Malaysia

Abstract: Purpose The present digital era has integrated the conventional telecommunications companies as service providers in this ever-competitive environment. Towards gaining business competitiveness, businesses are operated from the stance of dynamic business model that places focus on both economic activities and, more importantly, value-added benefits. One essential value embedded into business strategies refers to the aspect of sustainability in conjunction to environmental social governance (ESG). Within the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 92 publications
0
22
0
2
Order By: Relevance
“…The business strategy is vital in engaging corporate environmental practice to lower operating costs and emissions, enhance the reputation, obtain approval for operating license and boost stakeholder engagement. Besides, drivers, strategies and performance measures should be integrated into the business operation (Jasni, Yusoff, Zain, Md Yusoff, & Shaffee, 2019). This is also considering risk minimisation and operational efficiency, as the impacts were factored into daily operations and compliance.…”
Section: Introductionmentioning
confidence: 99%
“…The business strategy is vital in engaging corporate environmental practice to lower operating costs and emissions, enhance the reputation, obtain approval for operating license and boost stakeholder engagement. Besides, drivers, strategies and performance measures should be integrated into the business operation (Jasni, Yusoff, Zain, Md Yusoff, & Shaffee, 2019). This is also considering risk minimisation and operational efficiency, as the impacts were factored into daily operations and compliance.…”
Section: Introductionmentioning
confidence: 99%
“…ESG is being toted as one such key. Jasni et al (2019) have shown that ESG practices have been linked in other major studies to a decrease in risk-taking behavior of companies. This in turn has led to high-performing ESG companies to have a lower risk in terms of weighted-average cost of capital, meaning they are better able to generate sustainable investment returns.…”
Section: Sustainability For a Future-proof Economymentioning
confidence: 87%
“…ESG comprises stakeholder concerns around the environment, such as how the company can minimize waste and their carbon footprint, society, including socially considerate employment and workplace safety, and governance, which focuses on issues such as corporate fraud. According to Jasni et al (2019), ESG has begun evolving towards a new economic model – socially responsible investing (SRI). Performing well in the ESG Index allows potential investors to identify a company as a possible good investment, and this can only be achieved through wholesale embracing of ESG practices based on stakeholder expectations.…”
Section: Sustainability For a Future-proof Economymentioning
confidence: 99%
“…Sustainability in the oil and gas industry is a replication of the business model and the indicators of sustainable business models in this sector through production, reserve replacement percentage, gas sales, capacity, and sales. An investigation of ESG practices in the telecommunications business strategies of four Malaysian companies in 2015-using the content analysis methodology of annual reporting-described the business model as a dynamic model that copes with economic activities and presents ESG issues to stakeholders [91].…”
Section: Practicesmentioning
confidence: 99%